Housing development and PR1MA: myth or reality? - Sufian, Azlinor (2012)
One of the mechanisms in promoting housing development in a country is by having sufficient legal provisions regulating the land and development. Recently Malaysian Parliament has passed the new act relating to housing in Malaysia that is Perumahan Rakyat 1 Malaysia 2011(hereinafter referred to as “PR1MA”). It is alleged that the purpose of the Act inter alia to give opportunity to the middle income class citizens to buy houses where the corporation established through PR1MA will take care of the housing development. Nevertheless having read through the Act, it is observed that there are many ambiguities and uncertainties as to the functions of the corporation and how does the corporation will carry out such functions. This paper is aimed to analyse the provisions of PR1MA Act 2011 with the intention to present the strengths and weaknesses of the Act. As this paper will involve pure legal discussions, it will use the qualitative approach and the law and practices in Scotland may be referred to as comparison.